2015
DOI: 10.1002/14651858.cd011612.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and other glutamate receptor modulators for depression in adults

Abstract: We found limited evidence for ketamine's efficacy over placebo at time points up to one week in terms of the primary outcome, response rate. The effects were less certain at two weeks post-treatment. No significant results were found for the remaining ten glutamate receptor modulators, except for sarcosine being more effective than citalopram at four weeks. In terms of adverse events, the only significant differences in favour of placebo over ketamine were in regards to confusion and emotional blunting. Despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 150 publications
1
75
0
1
Order By: Relevance
“…Since mice deficient in the serotonin neurotransmitter showed reduced depression-like behavior and chronic administration of the SSRI fluoxetine lead to increased hippocampal neurogenesis [77], this may be a feasible medication to restore neurogenesis in adults. In preclinical and clinical studies a single treatment of the antidepressant ketamine has been sufficient to relieve depressive symptoms in adult patients and C57BL/6 mice previously exposed to chronic stress [78,79]. In humans, ketamine is known to relief symptoms in a very short period of time, but more investigation is needed to ameliorate or prevent associated side effects [79].…”
Section: Discussionmentioning
confidence: 99%
“…Since mice deficient in the serotonin neurotransmitter showed reduced depression-like behavior and chronic administration of the SSRI fluoxetine lead to increased hippocampal neurogenesis [77], this may be a feasible medication to restore neurogenesis in adults. In preclinical and clinical studies a single treatment of the antidepressant ketamine has been sufficient to relieve depressive symptoms in adult patients and C57BL/6 mice previously exposed to chronic stress [78,79]. In humans, ketamine is known to relief symptoms in a very short period of time, but more investigation is needed to ameliorate or prevent associated side effects [79].…”
Section: Discussionmentioning
confidence: 99%
“…The FSL also exhibits a dysfunctional regulation of glutamate transmission and has a reduction of both neuronal and glial glutamate receptors and transporters (Eriksson et al, 2012; Gomez-Galan et al, 2013). This is of relevance, given the accumulating evidence that suggests an aberrant glutamatergic signaling in humans with MDD (Sanacora et al, 2012) in combination with the promising role of novel antidepressant compounds that act as glutamate receptor modulators (Caddy et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Most of the recent trials on ketamine did not compare the efficacy of ketamine with other standard antidepressants [29]. The Cochrane Collaboration conducted a systematic review of previous ketamine trials and concluded that there was a limited superiority of ketamine over placebos in treating mood disorders [35, 36]. Hence, ketamine was not recommended to be used as an antidepressant.…”
Section: Discussionmentioning
confidence: 99%